ID: 155. Issue 1 (November 2015) - Heim, Markus
<x xml:space="preserve">Abstract</x> An estimated 70% of individuals infected with hepatitis C virus (HCV) develop chronic hepatitis (CHC) that can lead to cirrhosis and hepatocellular carcinoma. The innate immune system is central to host-virus interactions during the entire natural course of the disease. The viral escape mechanisms that result in persistent infections are poorly understood. In vitro, The HCV NS3/4A protease efficiently cleaves and inactivates two important signaling molecules in the sensory pathways that react to HCV pathogen associated molecular patterns (PAMPs) to induce interferons (IFNs), i.e. mitochondrial anti-viral signaling protein (MAVS) and Toll-IL-1 receptor domain-containing adaptor inducing IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qqx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> (TRIF). Despite this well documented viral escape mechanism, in vivo the innate immune system reacts to HCV within the first days after infection by inducing a strong IFN type I/III response. After 4–8 weeks, HCV specific T cells are recruited to the liver. IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7m9r" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives> stimulated genes get strongly expressed in the liver. In about 30% of patients the virus is eliminated during the acute phase of the infection by T cell mediated anti-viral mechanisms. In the remaining 70% of patients, HCV persists for decades. During this phase, T cell derived IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7m9r" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives> cannot be detected any more in liver biopsies. Instead, in about half of the patients, hundreds of type I or III IFN stimulated genes become again strongly expressed. However, this innate immune reaction is ineffective against HCV. Moreover, patients with constitutive IFN stimulated gene (ISG) expression have a poor response to treatment with pegylated IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rxr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> (pegIFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7n8q" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α)</alternatives> and ribavirin. The viral escape mechanisms that protect HCV from IFN mediated innate immune reactions are not entirely understood, but might involve blockade of ISG protein translation at the ribosome, localization of viral replication to cells with refractory IFN signal transduction pathways or to cell compartments that are not accessible to anti-viral IFN stimulated effector systems. Recently, genetic variations in the IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7p2x" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />λ</alternatives>4 gene locus were found to be strongly associated to spontaneous clearance of HCV and to response to treatment with pegIFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rxr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> and ribavirin. The finding supports a central role of the innate immune in host-viral interactions. The signaling pathways and cellular interactions that link genetic variants of IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7p2x" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />λ</alternatives>4 with immune answers to HCV remain to be elucidated.